2018
DOI: 10.1177/000313481808400127
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Wound Closure Techniques in Fournier's Gangrene

Abstract: Necrotizing soft tissue infection of the perineum, or Fournier's gangrene (FG), is a morbid and mortal diagnosis. Despite the severity of FG, the optimal definitive wound closure strategy is unknown, as are long-term wound outcomes. A retrospective review was performed over a 3-year period at a single trauma center. Patients were managed according to our institutional approach focusing on primary wound closure and secondary intention healing in residual wounds. Overall 168 patients were included. Complete prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Besides, the SOFA score remained its significance on logistic regression analysis. In the present study, the mean SOFA scores were calculated as 1.8 SD 1.1 and 3.8 SD 0.6 for survivors and non-survivors similar to the above mentioned study [7]. Besides, we showed its predictive power for mortality of FG.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Besides, the SOFA score remained its significance on logistic regression analysis. In the present study, the mean SOFA scores were calculated as 1.8 SD 1.1 and 3.8 SD 0.6 for survivors and non-survivors similar to the above mentioned study [7]. Besides, we showed its predictive power for mortality of FG.…”
Section: Discussionsupporting
confidence: 77%
“…The SOFA score has been used for identification of sepsis among patients who are critically ill [23]. Up to date, there is only one study in which the SOFA score was studied in FG patients [7]. In this study, the authors reported that lower mean SOFA scores (1.70 SD 2.30 vs. 2.98 SD 3.36) were significantly associated with the probability of primary wound closure.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“… CAD, coronary artery disease; CHF, congestive heart failure; PVD, peripheral vascular disease; CRF, chronic renal failure; ESRD, end-stage renal disease; HLD, hyperlipidemia; COPD, chronic obstructive pulmonary disease; HIV/AIDS, Virus Human Immunodeficiency/Autoimmune Deficiency Syndrome; GERD, gastroesophageal reflux disease; SLE, systemic lupus erythematous; MGUS, monoclonal gammopathy of undetermined significance. *A total of 92/111 Studies (N = 20; 259 cases) 4 , 6 9 , 11 – 34 , 36 38 , 40 45 , 49 52 , 54 62 , 64 , 66 72 , 74 , 76 85 , 87 , 89 , 91 – 104 , 106 – 111 …”
Section: Resultsmentioning
confidence: 99%